Composition of Genresof Bukhara Wedding Folklore - Yakhshibaevna, Sherbekova Gavkhar (European Journal of Life Safety and Stability (2660-9630), 2021)
In world folklore, ceremonial folklore, which expresses the national identity of the population living in different regions, and the peculiarities of the composition of these folklore genres, historical and genetic bases, structural-semantic, poetic, semantic, poetic, ceremonial songs. In particular, the genre structure, performance features, language, world of images of Bukhara wedding folklore are unique and require the study of the system as a whole.